DIGITAL KERYGMA: REEVALUASI TEOLOGIS DAN STRATEGI KOMUNIKASI VISUAL DALAM MENGHADAPI FRAGMENTASI INFORMASI DI MEDIA SOSIAL - Soewarto Tjokrohandoko; Gidion Gidion (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The development of the digital ecosystem has reconstructed the information consumption patterns of society, yet church institutions tend to be trapped in the phenomenon of ecclesiological lag. This study aims to critically evaluate the church's technocentric stuttering and formulate theological teaching strategies that are relevant while remaining faithful to the authority of Biblical revelation. Using a qualitative approach with an interpretive netnographic design, this research dissects the dialectic between the production of theological content and the reflective response patterns of audiences on video-based social media platforms. The results indicate that the current use of technology by the church is still pragmatic-instrumental, resulting in a reduction of pedagogical depth amidst information fragmentation. As a theoretical and practical solution, this study offers the Digital Kerygma framework through a Tiered Digital Pedagogy model. This model integrates three fundamental principles: Visual Theology as a hermeneutical tool, Narrative Theology as an existential bridge, and Reflective Fragmentation as a meaning condensation strategy. These findings confirm that the effectiveness of digital theological teaching is not determined by the duration of exposure, but by kerygmatic density, which is capable of transforming information fragments into cognitive initiation toward deep and sustainable spiritual formation.